Perancangan Peta Wisata Interaktif Kota Cilegon Sebagai Panduan Komprehensif Bagi Wisatawan - Wildan, Rian Agni; Gumelar, Rangga Galura (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2024)
The city of Cilegon has natural and cultural tourism potential that is worth visiting. This research aims to produce a digital, interactive, and comprehensive Tourist Map as an information channel and comprehensive Tourist Guide for both domestic and international tourists. This applied research uses a qualitative approach, with data collected from reliable sources such as official websites, tourism brochures, and interviews with local residents. The result of this research is an interactive and informative digital pamphlet in PDF format. The evaluation results of this Tourist Map show that it is highly useful and flexible, as the public can access the map digitally through new media (social media) or via traditional print media.